Comparative Analysis of Different Cryptographic Mechanisms of Data Security and Privacy in Cloud Environment - Sohal, Manreet; Sharma, Sandeep (International Journal of Computer Sciences and Engineering, 2018)
Cloud computing is an internet-based service which provides a platform based upon the internet for performing computations. In other words, it is the hiring of services from the service providers. But, since data has to be stored at the third party location, the data owners are always concerned about the security of their data. There are a number of security issues related to cloud computing. In this paper, a comprehensive review of various security challenges faced by the cloud has been presented. The major focus of this paper is the security of the data stored on the cloud. We have provided a detailed discussion on various cryptographic algorithms that have been proposed in recent years to ensure data security. These algorithms have been compared and analyzed based upon various security parameters and their pros and cons have been highlighted. This analysis opens up a new space that can be used to develop a new algorithm which can overcome the shortcomings of the existing algorithms and can enhance the security of the existing systems.